Stereotactic Radiosurgery for Vestibular Schwannomas: Reducing Toxicity With 11 Gy as the Marginal Prescribed Dose - Dupic, Guillaume; Urcissin, Marie; Mom, Thierry; Verrelle, Pierre; Dedieu, Véronique; Molnar, Ioana; El-Ouadih, Youssef; Chassin, Vincent; Lapeyre, Michel; Lemaire, Jean-Jacques; Biau, Julian; Khalil, Toufic (Frontiers in Oncology, 2020)
Background Stereotactic radiosurgery (SRS) is a common treatment option for vestibular schwannomas. Historically, a dose de-escalation of the marginal prescribed dose from 16 Gy to 12-13 Gy has been done to limit toxicity without reducing local control. We aimed to retrospectively report outcomes of Linac-based SRS for vestibular schwannomas treated with different doses. Methods Included in the study were 97 stage 1 (1%), 2 (56%), 3 (21.5%) and 4 (21.5%) vestibular schwannomas treated with Linac-based (Novalis®) SRS from 1995 to 2019. No margin was added to the GTV to create the PTV. The median marginal prescribed dose was 14 Gy (range: 12-16 Gy) before 2006 and then 11 Gy for all patients (61 pts). Mean tumor volume was 1.96 cm3, i.e. about 1.6 cm in diameter. Mean follow-up was 8.2 years. Results Following SRS, local control (LC) at 3, 5 and 10 years was 100%, 98.4% and 95.6% respectively (100% for those with ≤ 13 Gy as the marginal prescribed dose (NS)). Toxicity to the trigeminal nerve was reported in 7.2% of cases (3.3% and 0% for transient and permanent toxicity for 11 Gy). The marginal prescribed dose was the only significant predictive factor in univariate and multivariate analysis (HR = 1.77, 95% CI = 1.07–3.10, p = 0.028). Toxicity to the facial nerve was reported in 6.2% of cases. The marginal prescribed dose was again the only significant predictive factor in univariate and multivariate analysis (HR = 1.31, 95% CI = 0.77–2.23, p = 0.049). Conclusion Linac-based SRS for stage 1-3 vestibular schwannomas provides excellent outcomes: a 10-year local control rate of over 95%, with a permanent facial or trigeminal toxicity rate of under 5%. A marginal prescribed dose of 11 Gy seems to decrease nerve toxicity and facial toxicity in particular, without reducing local control. Prospective studies with longer follow-up are needed.